Effect of Finishing Auxilliaries on the Color Perception of Cotton Knit Fabric Dyed with Reactive Dye - Brahma, Shuvo; Islam, Md. Rashedul; Hossain, Emran; Dina, Rasheda Begum; Debnath, Smita Rani (European Scientific Journal, ESJ, 2018)
Dyed textiles are influenced by finishing treatments more or less strongly. Individual dyes as well as finishing products and conditions are responsible for this. An attempt has been made to assess the effects of some finishing auxiliaries on the color yield of reactive dyed cotton knit fabric. It was found that treatment with finishing auxiliaries decreased the shade depth to a considerable extent. The shade changes obtained after treating with fixing and soaping agent were found less than the treatment with caustic soda and combined caustic and glauber salt.